Brain Activation Induced by Myopic and Hyperopic Defocus From Spectacles - Kang, Meng-Tian; Wang, Bo; Ran, An-Ran; Gan, Jiahe; Du, Jialing; Yusufu, Mayinuer; Liang, Xintong; Li, Shi-Ming; Wang, Ningli (Frontiers in Human Neuroscience, 2021)
Purpose: To assess neural changes in perceptual effects induced by myopic defocus and hyperopic defocus stimuli in ametropic and emmetropic subjects with functional magnetic resonance imaging (fMRI). Methods: This study included 41 subjects with a mean age of 26.0±2.9 years. Mean spherical equivalence refraction was -0.54±0.51D in emmetropic group and -3.57±2.27D in ametropic group. Subjects view through full refractive correction, +2.00D myopic defocus and -2.00D hyperopic defocus in three random sessions. Arterial spin labeling perfusion was measured by fMRI to obtain quantified regional cerebral blood flow (rCBF). Behavioral tests including distant visual acuity (VA) and contrast sensitivity (CS), were measured every 5 minutes for 30 minutes. Results: Myopic defocus induced significantly greater rCBF increase in 4 cerebral regions compared with full correction: right precentral gyrus, right superior temporal gyrus, left inferior parietal lobule, left middle temporal gyrus. (P<0.001) The differences were less significant in low myopes than emmetropes. In the hyperopic defocus session, the increased responses of rCBF were only observed in the right and left precentral gyrus. Myopic defocused VA and CS improved significantly within 5 minutes and reached a plateau shortly after. Conclusion: This study revealed that myopic defocus stimuli can significantly increase blood perfusion in visual attention-related cerebral regions, which suggests a potential direction for future investigation on the relationship between retinal defocus and its neural consequences.